Religiosity and covid-19 preventive behaviour - Parrendah Adwoa Kpeli (University of Freiburg, Department of International Economic Policy (iep), 2024)
This study examines the impact of religiosity on preventive measures during the COVID-19 pandemic in the United States, specifically on mask usage, vaccine administration, booster doses, and the probability of testing positive for COVID-19. This study employs an extensive, recurrent dataset from 2020 to 2022 to analye the behaviors of many religious groups, focusing specifically on the differences between born-again and non-born-again Protestants. The results indicate that born-again Protestants exhibit a lower propensity to adhere to preventive measures, such as mask-wearing and immunisations. In contrast, non-born-again Protestants and Catholics demonstrate a higher likelihood of compliance with these guidelines. Unsurprisingly, born-again Protestants exhibit an increased propensity for testing positive for COVID-19 and are, therefore, more likely to have contributed to its heightened spread in the US. This research is essential for understanding the relationship between religiosity and health behaviours, as it emphasises the significant influence of religious identity on public health outcomes. It provides new insights into adherence to health directives, addressing significant gaps in the research by distinguishing among religious subgroups, analysing various preventative behaviours, and monitoring changes over an extended period throughout the United States.
Keywords: Z12; I12; I18; 330; Covid-19; religiosity; health behaviour